Cornerball: a new alternative sport proposal for school physical education - Diez-Fernández, Pelayo; Ruibal-Lista, Brais; Revesado-Carballares, David; Rodríguez-Cayetano, Alberto; López-García, Sergio (Frontiers in Sports and Active Living, 2024)
Physical Education has had to evolve and change throughout history to adapt to the demands of society. As a result, teachers have had to seek pedagogical alternatives to ensure that students are active, motivated, and engaged in the classroom. This approach allows for the development of motor, cognitive, and socio-emotional skills in students, ultimately contributing to the holistic development of the individual, which is the primary goal of education. Out of this intrinsic need for Physical Education, Alternative Sports have emerged, providing opportunities for different types of learning compared to more traditional sports. Cornerball, a hybrid between split-court and wall-based sports, played in a somewhat unique playing areaa 90º corner, is introduced with the aim of offering a new Alternative Sport. The objective of this descriptive study is to present a new pedagogical proposal designed for the educational context, highlighting its characteristics and fundamental aspects to consider, such as rules, the playing field, participants, and methodological strategies for its implementation within a Physical Education classroom. Therefore, the aims and purposes of this work are to describe a new sports game so that in the future, more detailed and specific empirical studies can be proposed.This document seeks to present a new pedagogical proposal designed for the educational context, highlighting its characteristics and the fundamental aspects to consider, such as the rules, the playing field, the participants, and methodological strategies to implement it within a Physical Education classroom. Con formato: Español (España) Código de campo cambiado Con formato: Hipervínculo, Español (España) Con formato: Español (España)